Relationship of choroidal thickness with pulsatile hemodynamics in essential hypertensive patients. Issue 5 (25th January 2021) - Mulè, Giuseppe; Vadalà, Maria; Sinatra, Nicola; Mancia, Ettore; Sorce, Alessandra; Geraci, Giulio; Carollo, Caterina; Montalbano, Katia; Castellucci, Massimo; Guarrasi, Giulia; Cillino, Salvatore; Cottone, Santina
Abstract: Controversy exists about the association of choroidal thickness (CTh) with blood pressure (BP) values. There is some evidence suggesting that central hemodynamics changes are associated with microvascular disease. Our study was aimed to assess the relationships between CTh and clinic and 24‐h BP and between CTh and estimated 24‐h aortic pulse pressure (aPP), 24‐h aortic systolic BP (aSBP), and 24‐h aortic augmentation index (aAIx) in a group of hypertensive patients. We enrolled 158 hypertensive subjects (mean age 48 ± 13 years) all of which underwent evaluation of the choroidal district by Swept‐Source optical coherence tomography (SS‐OCT) and 24‐h BP monitoring, in order to measure peripheral BP and to estimate central hemodynamic parameters. Inverse significant correlations of clinic PP, 24‐h aPP, 24‐h aSBP, and 24‐h aAIx with thicknesses of central ring, inner ring, and outer ring of the choroid and its overall average were found. The strongest of these correlations was that relating 24‐h aPP with overall average choroidal thickness ( r = −.531; P < .001). When we divided the study population in subjects with 24‐h aPP above and below the median value (35 mm Hg), CTh were thinner in subjects with higher values of 24‐aPP as compared to those with lower ones, even after adjustment for age, and other potential confounders. The relationships of CTh with 24‐h aPP remained significant also taking into account the effects of various covariates in linear multiple regression analyses. Our findings support the concept of a cross‐talk between macro‐ and microcirculation.